2018
DOI: 10.1186/s12904-018-0349-6
|View full text |Cite
|
Sign up to set email alerts
|

Does special education in palliative medicine make a difference in end-of-life decision-making?

Abstract: BackgroundCharacteristics of the physician influence the essential decision-making in end-of-life care. However, the effect of special education in palliative medicine on different aspects of decision-making in end-of-life care remains unknown. The aim of this study was to explore the decision-making in end-of-life care among physicians with or without special competency in palliative medicine (cPM).MethodsA questionnaire including an advanced lung cancer patient-scenario with multiple decision options in end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 69 publications
0
19
1
1
Order By: Relevance
“…Participants. In autumn 2015, a postal survey with a questionnaire was sent to 500 GPs who were randomly selected from the registry of the Finnish Medical Association [details published earlier by Piili et al (8,13)]. The survey was sent twice to non-respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Participants. In autumn 2015, a postal survey with a questionnaire was sent to 500 GPs who were randomly selected from the registry of the Finnish Medical Association [details published earlier by Piili et al (8,13)]. The survey was sent twice to non-respondents.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of gender is also unclear in end-of-life decisionmaking, as some studies have shown that female physicians are more in favour of active treatments and in some studies there is no gender-dependent difference in withholding or withdrawing life-sustaining treatments. [11,17,19,20,28] Only approximately 10% of the respondents in both years considered costs of care to influence their decisions, and the patient's social status was even less influential. Some studies do report that a patient's financial resources influence physicians' decision-making, [29] while our results probably reflect the Finnish health care system, where the cost of care are covered by the society with tax money.…”
Section: Factors Associated With Physicians' Decisionsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] The specialty of a physician impacts their decision-making, as oncologists have been shown to be more opposed to accepting the risk of hastening death by using high doses of drugs for symptom control compared to other specialties, but they are more willing to withhold or withdraw futile treatments in EOL-care. [12,16,17] Religion is shown to be associated with the unwillingness to withdraw lifesupportive care, [16,18,19] whereas age and gender of the physician are inconsistent factors in the decision-making. [11,17,[19][20][21] Decision-making should be consistent in the same types of clinical situations regardless of the physician who is responsible for the care of the patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ademais, os processos de tomada de decisão de interromper ou suspender terapias na prática clínica são impulsionados principalmente pela educação e a experiência clínica em CP, além das preferências do paciente. (Piili et al, 2018).…”
Section: Idadeunclassified